How Do Local Labor Markets and Human Capital Affect Employment Outcomes after Job Loss?. (4th April 2019) - Ueda, Ken
Abstract : This article uses the Longitudinal Employer‐Household Dynamics to evaluate how local industry concentration affects earnings losses for displaced workers. "Concentrated industries" are those industries with a high employment share within a labor market. This article compares earnings changes between displaced workers and job stayers within concentrated industries to the same within less concentrated industries. A separate comparison is made based on the expected level of job availability within the labor market. The findings show that earnings changes for displaced workers relative to job stayers are 7–13% higher within concentrated industries when job loss occurs during periods of high job availability. Earnings changes are 4.5–6% lower, however, when the same comparison is made during periods of low job availability. When firms are hiring workers, they are more likely to hire those previously employed within the same industry, since these workers have accumulated more relevant human capital.